The Attitude Towards National art In the Early Years of the Soviet Government In Turkestan - Nazarova Saodat (International Journal on Integrated Education, 2023)
The article covers the policy of the Soviet government in the early years based on archival sources. It mentions that the government used stage art to communicate its policies, decisions and orders to the people, and that it controlled the artistic idea of stage works displayed through its orders.